A neuropsychological profile and its correlation with neuroimaging markers in patients with subcortical ischaemic vascular dementia. (8th March 2023) - Tian, Rui; Zhang, Yanxin; Liu, Fang; Xue, Xinran; Zhang, Yutong; Tian, Zhuo; Fang, Tingting; Fan, Ruxue; Li, Yuan; Zhang, Nan
Abstract: Objectives: Cognitive and neuroimaging assessments are still the main clinical practice methods for screening and diagnosing vascular dementia (VaD) patients. This study aimed to establish the neuropsychological characteristics of mild‐to‐moderate subcortical ischaemic vascular dementia (SIVD) patients, find an optimal cognitive marker for differentiating them from Alzheimer's disease (AD) patients, and explore the correlation between cognitive function and total small vessel disease (SVD) burden. Methods: SIVD ( n = 60) and AD ( n = 30) patients and cognitively unimpaired healthy controls (HCs; n = 30) were recruited from our longitudinal MRI AD and SIVD study (ChiCTR1900027943) and received a comprehensive neuropsychological assessment and a multimodal MRI scan. Cognitive performance and MRI SVD markers were compared between groups. Combined cognitive scores were established for differentiating between SIVD and AD patients. Correlations between cognitive function and total SVD scores were analysed in dementia patients. Results: SIVD patients showed poorer performance in information processing speed and better performance in memory, language, and visuospatial function than AD patients, although all cognitive domains were impaired in both groups compared with HCs. Combined cognitive scores showed an area under the curve of 0.727 (95%CI 0.62–0.84, p < 0.001) for differentiating SIVD and AD patients. Auditory Verbal Learning Test recognition scores were negatively correlated with total SVD scores in SIVD patients. Conclusions: Our results suggested that neuropsychological assessments, specifically combined tests including episodic memory, information processing speed, language and visuospatial ability, are useful in the clinical differentiation between SIVD and AD patients. Moreover, cognitive dysfunction was partly correlated with MRI SVD burden in SIVD patients. Key points: Cognitive and neuroimaging evaluations are important in clinical practice for screening and distinguishing patients with subcortical ischaemic vascular dementia (SIVD) and Alzheimer's disease (AD). The complex features of cognitive impairment and MRI markers for vascular pathology (in particular small vessel disease (SVD)) and brain atrophy between patients with SIVD and AD are worthy of investigation. A combined cognition score, including episodic memory, information processing speed, language and visuospatial ability domains, was established to differentiate SIVD patients and AD patients, with a sensitivity of 75.0% and a specificity of 66.7%. Accumulating SVD burden on MRI was correlated with cognitive impairment to some extent in patients with SIVD, although the specific correlation for each MRI marker is still inconclusive.